Tracing the history of grounded theory methodology: from formation to fragmentation - Kenny, Meabh; Fourie, Robert (Qualitative report, 2014)
There are very few articles, which track the history of Grounded Theory (GT) methodology from its tentative conception to its present divisions. This journal article addresses the dearth by tracing the history of GT methodology from its conception in the 1960's, discussing the context of its composition, character, and contribution. Subsequently, the article follows the maturation of GT which is characterised by a series of contentious and, at times, antagonistic academic debates. The crux of these debates centres on disputes over core tenets of GT and have resulted in three dominant and divergent configurations of the GT methodology: Classic, Straussian, and Constructivist GT. These factions can often create confusion for the researcher wishing to embark on a GT study. However, an examination of the history of the GT methodology sheds light on the logic of these schisms. Keywords: Classic Grounded Theory, Straussian Grounded Theory, Constructivist Grounded Theory, History of Grounded Theory, Development of Grounded Theory, Differences between Grounded Theories, Grounded Theory Methodology, Glaser, Strauss and Corbin, Charmaz